Analysis of the Effect of Gross Domestic Product and Total Population on State Tax Revenue (2016-2020) - Lisda Aisyah Aisyah; Meichio Lesmana Lesmana; Muhammad Sauqi Sauqi; Agus Alimuddin Alimuddin (Faculty of Economics and Management, 2022)
Taxes are the main sector that provides income to the state, from which these funds will be used to finance the running of various sectors in Indonesia. Therefore, to advance the country a policy is needed by optimizing tax revenue, and each taxpayer must fulfill its obligation to pay taxes. The purpose of this research is to determine the factors that influence the amount of national tax revenue in Indonesia. From the theory obtained and from several previous studies, there are several factors that influence tax revenue, including the Gross Domestic Product (GDP) and population. The data used in this study are secondary data for the period 2016 to 2020 taken from the official website, namely the Central Statistics Agency (BPS) and the Ministry of Finance of the Republic of Indonesia, which are then analyzed using multiple regression analysis. The results of this research indicate that the gross domestic product (GDP) and population variables simultaneously and partially has an effect on state tax revenue at the 5% and 1% significance levels while when viewed through Islamic principles, Gross Domestic Product (GDP) reaches 80 percent so that GDP of Indonesia is recorded at around USD 1 trillion or equivalent to Rp. 14.04 trillion.